Parameters in Canines After Cesarean Sections - Conze, Theresa; Büttner, Kathrin; Wehrend, Axel (Frontiers in Veterinary Science, 2022)
This study evaluated fertility in canines after caesarean section and compared it with natural parturition. Parameters like the time of the next heat after the first parturition or caesarean section, which heat was used for another breeding attempt, whether it was successful, number of puppies that were born, and the necessity of another caesarean section were examined. The study relied on questioning patient owners at a University clinic. A Google online form was also used. Information for 261 dogs from different breed groups was included, of which 119 bitches were in the caesarean section group, and 142 were in the natural parturition group. 93 ± 2.7 % (LSMeans ± standard error) and 91.12 ± 3 % (LSMeans ± standard error) of the bitches became pregnant after caesarean section and natural parturition at the first breeding attempt. There was no significant effect of the breed or whether the bitch had undergone a caesarean section before (p = 0.8 and p = 0.63). Bitches, which underwent a caesarean section, were more likely to have further caesarean sections performed (p < 0.001). However, neither the breed groups (p= 0.17), whether the bitch had undergone a caesarean section (p = 0.59) nor the number of previous parities had any effect on the number of puppies born (p = 0.95). The breed group bulldogs had a high proportion of caesarean sections, Only 42.11 % of the bulldogs had a natural parturition as the first included parturition and only 31% gave birth naturally thereafter.